Retrospective evaluation of factors influencing successful skin grafting for patients with skin cancer of the foot. Issue 9 (13th April 2017) - Goto, Hiroyuki; Yoshikawa, Shusuke; Mori, Keita; Otsuka, Masaki; Omodaka, Toshikazu; Yoshimi, Kosuke; Yoshida, Yuichi; Yamamoto, Osamu; Kiyohara, Yoshio
Abstract: Skin grafting is a simple method for reconstruction of a large defect on the foot. Although skin grafting on the foot sometimes fails, it is not clear what factors influence the success rate of skin grafting. We analyzed data for 71 patients with skin cancer of the foot who underwent reconstruction of defects with skin grafting. The factors we evaluated were success rate of skin grafting, weight‐bearing or non‐weight‐bearing area, immediate or delayed reconstruction, and whether a tie‐over bolster was used or not. The success rates were higher in patients with lesions in non‐weight‐bearing areas than in patients with lesions in weight‐bearing areas and in patients who underwent delayed reconstruction than in patients who received immediate reconstruction. On the other hand, the use of a tie‐over bolster did not improve the success rate. In conclusion, delayed reconstruction is desirable if the lesion is located in a weight‐bearing area.